2014
DOI: 10.1103/physrevb.89.205105
|View full text |Cite
|
Sign up to set email alerts
|

Kondo holes in topological Kondo insulators: Spectral properties and surface quasiparticle interference

Abstract: A fascinating type of symmetry-protected topological states of matter are topological Kondo insulators, where insulating behavior arises from Kondo screening of localized moments via conduction electrons, and non-trivial topology emerges from the structure of the hybridization between the local-moment and conduction bands. Here we study the physics of Kondo holes, i.e., missing local moments, in three-dimensional topological Kondo insulators, using a self-consistent real-space mean-field theory. Such Kondo hol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 78 publications
(119 reference statements)
0
24
0
Order By: Relevance
“…This includes a proper symmetric phase structure that leads to the topological characteristics of SmB 6 . In fact, the community has recently witnessed a renewed focus in the designing of model topological Hamiltonians for SmB 6 (and systems alike) [36][37][38][39][40][41]. Note, however, that this issue of global topology is a lower-energy physics emerging below the higher-energy local Kondo gap scale.…”
Section: Resultsmentioning
confidence: 99%
“…This includes a proper symmetric phase structure that leads to the topological characteristics of SmB 6 . In fact, the community has recently witnessed a renewed focus in the designing of model topological Hamiltonians for SmB 6 (and systems alike) [36][37][38][39][40][41]. Note, however, that this issue of global topology is a lower-energy physics emerging below the higher-energy local Kondo gap scale.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction of the nuclear spin with the topological surface states is via a contact exchange, 21, 33 We assume that the exchange coupling of the nuclear spin is with the true spin. If the full f -states are considered, the orbital degree of freedom of the crystalline field Kramers doublet has to be traced out, yielding renormalizations of the expectation values of the Pauli matrices, which can be absorbed into the exchange coupling defined below.…”
Section: A Nmr Hamiltonianmentioning
confidence: 99%
“…Arrows denote the spin texture of the surface carriers corresponding to the ground state configuration with the Γ8 quartet of the f -levels. 19,21 We assume that chemical potential crosses all three bands. Without loss of generality we consider the bands with the same chirality.…”
Section: Introductionmentioning
confidence: 99%
“…7 In particular, SmB 6 -a material in which strong hybridization between samarium conduction d-electrons and strongly correlated f -electrons drives an onset of an insulating state at low temperatures [8][9][10][11][12] -has recently came into focus of theoretical and experimental studies as a most prominent candidate for the first correlated topological insulator. [13][14][15][16][17][18][19][20][21][22][23] In order to experimentally establish the existence of the helical conduction time-reversal invariant states on a surface of a generic topological insulator using either transport or thermodynamic measurements, one needs to show that (i) the conduction at low temperatures is limited to the surface and (ii) single particle states have linear momentum dispersion along the surface and no dispersion in the normal to the surface direction and (iii) there is a strong spin-orbit interaction, which leads to coupling between the momentum and spin of the conduction electron giving rise to the helicity of the carriers. In samarium hexaboride, a series of state-of-the-art transport studies have unambiguously shown that the resistivity plateau at temperatures below 5 Kelvin 8,9 is governed by surface conduction only.…”
Section: Introductionmentioning
confidence: 99%